2014
DOI: 10.1007/s00417-014-2602-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for the estimation of the general height of the visual field in patients with glaucoma

Abstract: Background More accurate estimation of the general height of the visual field may improve our ability to detect and monitor progression of diseases affecting visual function such as glaucoma. General height (GH) can be affected by factors such as cataracts, pupillary miosis, refractive error, and learning and fatigue effects. The conventional GH index, consisting of subtracting the 85th largest value from the total-deviation map, has been shown to overestimate the height in patients with moderate and advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These correspond to 25 and 28 dB, respectively, on the HFA. 14 These two contrast levels were used to compensate for differences in the height of the hill of vision 15 100% contrast would be appropriate for those with a low hill of vision and 50% contrast for a high hill of vision. For each contrast level, one presentation of the stimulus was made at each location, selected randomly.…”
Section: Methodsmentioning
confidence: 99%
“…These correspond to 25 and 28 dB, respectively, on the HFA. 14 These two contrast levels were used to compensate for differences in the height of the hill of vision 15 100% contrast would be appropriate for those with a low hill of vision and 50% contrast for a high hill of vision. For each contrast level, one presentation of the stimulus was made at each location, selected randomly.…”
Section: Methodsmentioning
confidence: 99%
“…The 24‐2 total deviation values were obtained from the patients’ routine clinic visits with the Humphrey Field Analyzer using a G‐III stimulus. The total deviation maps provided a raw estimate of the perimetric deviation from age norms without further adjustments to the data such as in a pattern deviation map, which uses a method that can overestimate the adjustment factor in eyes with perimetric defects 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…We have found that forced‐choice methods can reduce between‐visit variability in glaucomatous defects by a factor of two as compared to perimetry . Perimetric indices provide an adjustment for homogeneous fluctuation with the ‘pattern deviation’ (PD) analysis, which attempts to compensate for fluctuations in the height of the hill of vision but is known to have limitations . In a follow‐up analysis we used PD to estimate the height of hill of vision, but correcting for this did not reduce variability in ganglion cell number.…”
Section: Discussionmentioning
confidence: 99%
“…39 Perimetric indices provide an adjustment for homogeneous fluctuation with the 'pattern deviation' (PD) analysis, which attempts to compensate for fluctuations in the height of the hill of vision but is known to have limitations. 40 In a follow-up analysis we used PD to estimate the height of hill of vision, but correcting for this did not reduce variability in ganglion cell number. The determination of visual progression in logarithmic units appears to be more robust than determination of visual progression in ganglion cell numbers.…”
Section: Discussionmentioning
confidence: 99%